The vampire Armand - Rice, Anne 1941- (New York Ballantine Books, 1999)
The vampire's story, from his boyhood in Kiev, his enslavement to a vampire masquerading as a Venetian painter, and his dedication to his two mortal children.
Originally published: New York : Alfred A. Knopf, 1998.
Keywords: Vampires -- Fiction; Renaissance -- Fiction; Kiev (Ukraine) -- Fiction; Venice (Italy) -- Fiction; Paris (France) -- Fiction; New Orleans (La.) -- Fiction; Occult fiction; Horror tales